Estrategia 3.0 para la optimización del engagement de servicio en institutos médicos privadas de servicio público. Caso “Solca Núcleo Quito” - Barros Mosquera, Andrea Estefanía (2015)
In Ecuador there are very few non-profit organizations that actually invest in advertising, which limits their ability to accomplish their goals. SOLCA being one of them, counts with limited communication actions that keep people and business from investing in their cause. These issues ad up with the fact that each year there is an increasing amount of patients and governmental changes that limits the budget of the hospital affecting their everyday work. Therefore there is the need to develop a 3.0 communication strategy that will reach a target that might be interested in getting involved with the cause while informing ´people about cancer. The goal is to raise funds for the hospital by touching the sensitive fibers of people making them wonder about their own reality. The strategy will involve online actions, print material and below the line activities that reflect the target’s behavior and the limited budget of the hospital. This will guarantee an optimization while reaching a lot of people that translates to a maximum exposure of the message. The result will be an strategic communication plan for SOLCA with the possibility of application in similar foundations, hospitals or institutions, that achieves the much needed long term engagement with the audiences and enterprises interested in making a difference in a win/win scenario for both parts involved.